2016
DOI: 10.4070/kcj.2016.46.6.827
|View full text |Cite
|
Sign up to set email alerts
|

Endocan and Non-Dipping Circadian Pattern in Newly Diagnosed Essential Hypertension

Abstract: Background and ObjectivesNon-dipper hypertension is frequently accompanied by endothelial dysfunction and activation. Previous studies suggested that endocan may be a novel endothelial dysfunction marker. This study aims to investigate the association between circadian blood pressure (BP) pattern and plasma endocan levels together with high-sensitivity C-reactive protein (hsCRP) in patients with newly diagnosed untreated hypertension.Subjects and MethodsTwenty-four hour ambulatory blood pressure monitoring was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Oktar et al have recently evaluated plasma endocan levels in patients with newly diagnosed HT [ 27 ]. Significantly elevated endocan levels in HT have already been reported in previous studies [ 28 , 29 ]. However, the study by Oktar et al was the first to indicate that microalbuminuria is elevated in patients with newly diagnosed HT and that it positively correlates with endocan concentrations.…”
Section: Endocan In Ckdsupporting
confidence: 77%
“…Oktar et al have recently evaluated plasma endocan levels in patients with newly diagnosed HT [ 27 ]. Significantly elevated endocan levels in HT have already been reported in previous studies [ 28 , 29 ]. However, the study by Oktar et al was the first to indicate that microalbuminuria is elevated in patients with newly diagnosed HT and that it positively correlates with endocan concentrations.…”
Section: Endocan In Ckdsupporting
confidence: 77%
“…Finally, 15 articles involving a total of 3097 subjects met the inclusion criteria for our meta-analysis. [923] Of these, there were 8 papers about coronary artery disease (CAD), [10,12–18] 6 about hypertension, [9,11,15,16,22,23] and 3 about coronary flow slow [19–21] (Table 1). A flowchart of the study selection progress with specific reasons for exclusion is displayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have suggested that higher BP in hypertensive patients during the night might lead to greater endothelial damage. Furthermore, greater endothelial damage would lead to higher levels of nocturnal BP 4,49. Isolated nighttime hypertension might predict cardiovascular events 52.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension, a common chronic condition that affects up to 40% of human adults,13 is a major risk factor for stroke, heart attack, and other vascular as well as renal and metabolic diseases 2,47. Hypertension, which is associated with target organ damage (TOD),8 is a serious cause of cardiovascular and cerebrovascular diseases 9.…”
Section: Introductionmentioning
confidence: 99%